Values of Friendship in Animation Movie Angry Birds: A Semiotic Analysis - Oktaviani, Bella Surya; Nugroho, Abdillah (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The aim of this research is to analyze the value of friendship in Angry Birds movie (2016). This qualitative descriptive study involves observing and analyzing the film's content to identify moments that highlight interactions between characters, their behaviors, and language use, all related to the importance of friendship. The researcher employs Roland Barthes' semiotic analysis method, where each scene contains signs that construct a myth depicting friendship. The findings of the study offer valuable lessons on friendship, emphasizing teamwork, trust, and overcoming differences. The film also highlights virtues such as sacrifice, loyalty, and togetherness in adversity, which can be applied to real-life relationships.